Communication and popular imagination - Veron, Eliseo (2018)
This work, when proposed as the outline of an extremely vast and complex problem, obliges to present in a necessarily schematic manner and within the available space the issues addressed. The reader is invited to complete this reading, especially in relation to the problem of ideology.